Modèles D’estimation De L’émission Du Méthane Entérique Des Animaux D’élevage Au Maroc - F.Z, Laabouri; A., Guerouali; A. S., Alali; M., Maghfoul (European Scientific Journal, ESJ, 2018)
Enteric CH4 emissions have been of great scientific interest as they represent a real energy loss for livestock and are also responsible for global warming. The objective of this study is to measure enteric methane emissions in farm animals, and then develop models for estimating quantities emitted based on the amount of dry matter ingested (MSI). Holstein cows (n = 38) received dietary rations of 50% forage and 50% feed concentrate, and a linear regression model was developed to predict CH4 production per animal (g). CH4 (animal / day) from the amount of dry matter ingested and the equation obtained was as follows: Y = 19.05X. Here, Y is the amount of CH4 (g CH4 / cow / day) and X is the amount of ingested dry matter (kg), with R² = 0.91, r = 0.97, and RMSPE = 5.53%. For small ruminants (n = 22), three dietary levels were used and methane production was measured. In addition, the equation obtained was: Y = 12.21 X with R² = 0.81, r = 0, 91 and RMSPE = 15.80%. In camelins (n = 12) and equines (n = 10), only one food level was used and methane measurements did not develop an estimation model. However, mean values of methane production were determined and they corresponded to 11.41 g CH4 / kg MSI in camels and 2.18 g CH4 / kg MSI in horses.